EPISTEMOLOGI ILMU DAKWAH KONTEMPORER - Khusnul Khotimah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2016)
The existence of contemporary da’wa needs to be brought closer to science, particularly in the face of contemporary problems of today. Islam as a religion rahmatal lil ‘Alamin should be able to contribute and also a solution to the development and changes of modern society. During this time the Islamic civilization, Islam stagnating even impressed away from the bustle of the world of science. If we look back, it is Islam as a pioneer of the findings of science which later developed by Western civilization. science and civilization of the world today, that are in the Mecca of Western civilization and Islamic civilization seemed to stagnate without any significant progress for the benefit of the Ummah. Setbacks science in Islam was triggered by deprivation of thinking Muslims with the closing of the doors of ijtihad plus scientific epistemology of classical Islamic discourse that is patterned Ghazalian (sect Al-Ghazali) the latter is more dominant. So do not be surprised if the findings achievement in the field of science and technology is far less than the West or even in the Muslim world scientific findings hardly be said not ada.Agar propagation of Islam back in concern with the vision of science as in the early days of the Islamic scientific civilization, there are several bids epistemology and method propaganda through contemporary Muslim scholarship, which now needs to be tested by backtracking to do the integration of science and religion by trying to use a knife four paradigm offered by Ian Barbour, namely, typology of conflict, independence, dialogue and integration. Besides the need for redefenisi or reconceptualization of the discourse of integration of science and religion in science Islam. Keberadaan dakwah kontemporer perlu didekatkan dengan sains, terutama dalam menghadapi masalah-masalah kontemporer dewasa ini. Islam sebagai agama rahmatan lil ‘alamin harus mampu memberikan kontribusi dan sekaligus solusi terhadap perkembangan dan perubahan masyarakat modern. Selama ini peradaban Islam, mengalami stagnan bahkan Islam terkesan menjauh dari hiruk-pikuk dunia sains. Kalau kita menengok ke belakang, justru Islam sebagai pelopor terhadap temuan-temuan sains yang kemudian dikembangkan oleh peradaban Barat. Ilmu pengetahuan dan peradaban dunia sekarang ini, kiblatnya berada pada peradaban Barat dan seakan-akan peradaban Islam mengalami stagnan tanpa ada kemajuan yang signifikan untuk kemaslahatan umat. Kemunduran sains dalam Islam dipicu oleh pemasungan pemikiran umat Islam dengan ditutupnya pintu ijtihad ditambah lagi wacana epistemologi keilmuan Islam klasik yang berpola Ghazalian (mazhab Al-Ghazali) yang belakangan lebih dominan. Tidak heran kalau prestasi temuan di bidang iptek kalah jauh dari orang Barat, bahkan dalam dunia muslim temuan sains hampir dikatakan tidak ada. Agar dakwah Islam kembali concern dengan visi sains seperti pada awal-awal peradaban keilmuan Islam, ada beberapa tawaran epistemologi dan metode dakwah melalui keilmuan muslim kontemporer, yang saat ini perlu dicoba dengan melakukan pelacakan kembali untuk melakukan integrasi sains dan agama dengan menggunakan pisau empat paradigma yang ditawarkan oleh Ian Barbour yaitu: tipologi konflik, independensi, dialog, dan integrasi. Selain itu perlu adanya redefenisi atau rekonseptualisasi terhadap wacana integrasi sains dan agama dalam keilmuan dakwah Islam.